Copper metabolism in hepatocellular carcinoma: from molecular mechanisms to therapeutic opportunities - Pang, Ziling (Frontiers in Molecular Biosciences, 2025)
Copper is a vital trace metal that facilitates cell proliferation, angiogenesis, and tumour spread. The liver is essential for copper metabolism, hence regulating copper levels is crucial for hepatic health. Hepatocellular carcinoma is a primary liver cancer characterised by a high death rate, and extensive research has shown the substantial impact of copper on its progression. This research primarily examines the molecular mechanisms involved, summarises the regulation of copper homeostasis, and addresses the role of copper metabolism in the promotion and inhibition of hepatocellular carcinoma development. Furthermore, it investigates prospective clinical approaches for targeting copper in the treatment of this disease, intending to establish a theoretical basis for the clinical use of copper in the management of hepatocellular carcinoma.